Ethical leadership and workplace behavior in the education sector: The implications of employees' ethical work behavior - Guo, Fengrui; Xue, Zhongyi; He, Jiaxu; Yasmin, Fakhra (Frontiers in Psychology, 2023)
The main purpose of this research is to examine the effect of ethical leadership on employees' ethical work behavior. Furthermore, this research examines the mediating role of organizational commitment in the relationship between ethical leadership and employees' ethical work behavior. The study has been conducted in public sector educational organizations, and 500 questionnaires were distributed among targeted employees. Out of these, 400 valid responses were received from the individuals working in education sector in China. The findings of the study show a positive and significant impact of ethical leadership on employees' ethical work behavior. Organizational commitment also significantly mediates the relationship between ethical leadership and employees' ethical work behavior. The practical implication of the current study is useful for all organizations in the public sector. As ethical leadership is positively related to employees' work behavior, we suggest that organizations should develop and conduct such training programs to enhance ethical work behavior. The leaders, having an ethical vision, should be appointed to stimulate ethical work behavior within the organization. Furthermore, organizations can conduct management training programs, seminars, and workshops to encourage such behavior. Ethical behavior can be encouraged among employees by clearly making it a necessary role within job requirements. Top management and leadership need to educate the employees regarding the worth and need of ethical behavior in the workplace to achieve positive outcomes